Faktor yang Mempengaruhi Penerimaan Klien di KAP Second Tier - Tunjungsari, Dinda; Amrullah, Fitriany (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to explore the factors that influence client acceptance decisions at Second Tier Public Accountant Firms (PAF). In this study, researchers used quantitative data by distributing questionnaires to companies that requested audit services to PAF Second Tier during 2022, 2023, and 2024 supported by interviews and obtaining financial statement data. The PAF that was used as a sampling site was PAF operating in Jakarta and included in the second tier category, which was determined based on the number of public accountants incorporated and the classification of PAF according to data from PPPK. The results showed that management integration and audit fees have a significant positive effect on client acceptance decisions. In addition, audit risk and PAF business risk have a negative effect on client acceptance decisions. Conversely, client business risk has no effect on client acceptance decisions. This is because the client's business risk is not directly related to the image and sustainability of PAF so that PAF does not prioritize it in client acceptance decisions.